Tunisia Public Expenditure Review : A New Pact for the Transition - Modernizing the State for Better and Fairer Public Spending - World Bank (World Bank, Washington, DC, 2020)
Tunisia faces the challenge of improving the quality of its public spending and maintaining fiscal sustainability following a decade of weak economic performance. It is critical for Tunisia to strengthen the quality of infrastructure and services, and to support inclusive growth and private sector job creation. The aim of this public expenditure review (PER) is to identify structural policy options to help Tunisia tackle its economic and social challenges through more effective and equitable public spending. This PER employs a rich set of detailed spending data at the level of the central government and state-owned enterprises (SOEs) to analyze how public expenditures in Tunisia can be allocated and spent in a more effective and equitable manner. The report also assembles detailed expenditure, operational, and financial data from SOEs with a focus on the energy, water, roads, and public transport sectors. These data allows to analyze and benchmark Tunisia’s spending trends, effectiveness, and equity, and to identify areas in which spending growth can be contained, where spending gaps exist, where resetting of spending priorities is needed and reallocation of expenditures necessary, and where spending should be more balanced to reduce inequities. The PER is organized in three blocks. The first block - composed of chapters one to four - analyzes the macro-fiscal profile and the two largest spending items, namely wages, energy, and food subsidies, as well as the single largest liability, namely pensions, and the social protection system which is critical for protecting vulnerable households from shocks and from the potential negative effects of certain reforms. The second block - composed of chapters five and six - covers the education and health sectors, the two most important social services for human capital development, which account for the largest share of social spending. The third block - composed of chapters seven to nine -analyzes the issues of public investment efficiency and SOE performance in the electricity, water, roads, and transport sectors.